2019
DOI: 10.1159/000499313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of the Allplex<sup>TM</sup> Respiratory Panel 1 Test Compared to Simplexa<sup>TM</sup> Flu A/B and RSV for Detection of Influenza Virus and Respiratory Syncytial Virus Infection Including Their Subtyping

Abstract: Objective: TheAllplexTM Respiratory Panel 1 (ARP) is a new assay based on a real-time polymerase chain reaction (RT-PCR) for the detection of influenza A (Flu A), influenza B virus (Flu B), and respiratory syncytial virus (RSV), including subtyping by multiple detection temperature (MuDT) technology. We evaluated the performance of the Allplex Respiratory Panel compared to the SimplexaTM Flu A/B & RSV assay (SP) and other diagnostic tools. Materials and Methods: A total of 372 samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In general, our findings are consistent with the PPA/sensitivity values reported in previous studies for influenza A and B 7,9,15‐20 . For RSV, however, although the NPA values are within the ranges of the previous reports, 7,9,15‐20 Xpert ® Flu/RSV detected less RSV cases than Allplex ™ RP1 (42 vs 54 positive cases) and the PPA was 77.8% in our study. This PPA value was lower than the findings of Gimferrer et al 15 and other studies which reported PPA/sensitivity values of 91%‐100% for RSV 9,18‐20 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In general, our findings are consistent with the PPA/sensitivity values reported in previous studies for influenza A and B 7,9,15‐20 . For RSV, however, although the NPA values are within the ranges of the previous reports, 7,9,15‐20 Xpert ® Flu/RSV detected less RSV cases than Allplex ™ RP1 (42 vs 54 positive cases) and the PPA was 77.8% in our study. This PPA value was lower than the findings of Gimferrer et al 15 and other studies which reported PPA/sensitivity values of 91%‐100% for RSV 9,18‐20 .…”
Section: Discussionsupporting
confidence: 92%
“…It is an important measure to rule‐out a disease when the test result is negative 25 . In general, our findings are consistent with the PPA/sensitivity values reported in previous studies for influenza A and B 7,9,15‐20 . For RSV, however, although the NPA values are within the ranges of the previous reports, 7,9,15‐20 Xpert ® Flu/RSV detected less RSV cases than Allplex ™ RP1 (42 vs 54 positive cases) and the PPA was 77.8% in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations